1986
DOI: 10.1128/jb.167.2.587-593.1986
|View full text |Cite
|
Sign up to set email alerts
|

Linear plasmidlike DNA in the plant pathogenic fungus Fusarium oxysporum f. sp. conglutinans

Abstract: Double-stranded, 1.9-kilobase-pair (kbp) DNA molecules were found in 18 strains representing three pathogenic races of Fusarium oxysporum f. sp. conglutinans. The DNA element (pFOXCl) from a race 1 strain and the DNA element (pFOXC2) from a race 2 strain were shown by restriction endonuclease mapping to be linear. pFOXC2 was found in mitochondrial preparations and appears to have blocked 5' termini, as it was sensitive to 3' --5' exonuclease HI but insensitive to 5' -) 3' A exonuclease. The major 1.8-kbp BgII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…This indicated that the autonomous plasmids differ from the linear mitochondrial plasmid found in F. oxysporum from which pFT1 was partially derived. Mitochondrial plasmids band with the mitochondrial DNA fraction in the presence of bisbenzimide (14). The banding of the autonomous plasmids with nuclear DNA in CsCl-ethidium bromide gradients suggested that the plasmids were linear.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…This indicated that the autonomous plasmids differ from the linear mitochondrial plasmid found in F. oxysporum from which pFT1 was partially derived. Mitochondrial plasmids band with the mitochondrial DNA fraction in the presence of bisbenzimide (14). The banding of the autonomous plasmids with nuclear DNA in CsCl-ethidium bromide gradients suggested that the plasmids were linear.…”
Section: Resultsmentioning
confidence: 97%
“…1) was constructed as follows: a 1.8-kilobase (kb) fragment from pFOXC2, the linear mitochondrial plasmid endogenous to F. oxysporum f. sp. raphani, was cloned into pUC12, producing pCK1 (14). A 2.4-kb SaiI fragment from pDH25 (6), which contains the bacterial hygromycin B phosphotransferase gene (hph) driven by the Aspergillus nidulans trpC promoter, was ligated into the single Sail site of pCK1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmids pFOXC2 and pFOXC3 are 1.9-kb linear DNAs that reside in mitochondria of certain forma specialis of the fungal plant pathogen Fusarium oxysporum (17). The plasmids are classified as retroplasmids because they each encode a reverse transcriptase (RT) and replicate via an RNA intermediate (18,24).…”
mentioning
confidence: 99%